PENDAMPINGAN MASYARAKAT DALAM PENGGUNAAN APLIKASI KAWAL DESA DI DESA CISURUPAN - Mulyani, Asri; Nugraha, Aldi; Jamaludin; Khaifa, Raisha Sarah; Maulud, Restu Bagja; Oktavian, Muhamad Ar Rasyid Rizki; Sugriantha, Irham; Ismaya, Karina; Salsabila, Kailla; Setiawan, Ahmad Dandi; Homsatin, Asyifa Azsma; Muhamad, Zaki; Rizki, Riyandi Muhamad; Janatunnisa, Raisya Agni; Ramdani, Dikri; Pasundan, Gia Aghista; Abdurrohman, Muhammad Akmal; Saputri, Amellia; Akbar, Fazri Haikal; Oktavian, Zordan; Rangga, Wisnu (Institut Teknologi Garut, 2025)
Village fund management requires transparency and community participation. One effort to support this is the implementation of the Kawal Desa application as a digital solution. This community service activity aims to enhance the digital literacy of village officials and residents, as well as to strengthen oversight of village fund usage. Methods employed include workshops, distribution of materials, and application usage demonstrations. The results indicate an improved understanding among village officials and residents in operating the application, leading to more transparent and efficient village services. This activity contributes to fostering collaboration between village authorities and the community toward more informative and integrated village governance.